GOVERNMENT FUNDING AND SMALL AND MEDIUM SCALE ENTERPRISES PERFORMANCE IN LAGOS STATE, NIGERIA - Ishaku Danladi (International Journal of Innovations in Engineering Research and Technology, 2021)
Over the years, government of Nigeria has funded Small and Medium Enterprises (SMEs) by establishing various financial institutions and regulate them for the purpose of enhancing the growth of SMEs in the country, yet the performance of SMEs is not commensurate with the funding released to these institutions. The study therefore examines government funding on the promotion and development of SMEs in Lagos State, Nigeria. The research design used for the study is survey method. The sources of data collection is primary sources of data through the use of questionnaire. The population of the study is 3818 and the sample size used for the study is 400 respondents, the sampling techniques used is stratified random sampling. The method of data analysis is through simple percentages for descriptive data and multiple regression for test of hypotheses. Based on the analysis, the following were the findings of the study; Bank of Industry Funding has positive significant impact on SMEs performance in Lagos State. Bank of Agriculture funding to SMEs help in the promotion and development of the performance of their businesses. Based on the findings, the study concluded that the roles of government funding on the promotion and development of SMEs in Nigeria is very low and do not help in the growth of businesses in Nigeria. The study recommends that government of Nigeria should try to make it easier to access the various scheme of financing SMEs in the country accessible. Adequate fund should be channeled to SMEs through these schemes and the conditions attached in accessing the loans should not be stringent enough to prevent SMEs owners from having access to them.